Pharmaceutical cocrystal and their role in improving solid state properties of active pharmaceutical ingredients - Ameera A Radhi; Iman S Jaafar; Noor S Jaafar; Sarah M Faisal (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2023)
Cocrystallization is an emerging approach for improving physico-chemical characteristics of an active pharmaceutical ingredient (API) for instance dissolution rate, solubility, stability in addition to mechanical